COLONIAL DOMINATION AND INDIGENOUS RESISTANCE IN AVATAR (2009): A POSTCOLONIAL ANALYSIS - Izhar Fadli; M. Manugeren M. Manugeren; Burhanuddin Arafah; Saiful Matondang (BASIS (Bahasa dan Sastra Inggris), 2026)
Abstract This study examined the representation of colonial power and indigenous resistance in James Cameron’s Avatar through a postcolonial perspective. The film depicted the conflict between human colonizers and the Na’vi, the indigenous inhabitants of Pandora, reflecting patterns of historical colonial expansion and resource exploitation. The research applied postcolonial theories proposed by Edward Said, Homi K. Bhabha, and Gayatri Chakravorty Spivak to analyze the ideological structures within the film. A qualitative descriptive method was used, focusing on narrative elements, character representation, dialogue, and visual symbolism. The analysis showed that the human corporation represented colonial domination, economic exploitation, and cultural imperialism, while the Na’vi embodied indigenous identity, ecological harmony, and collective resistance. The character of Jake Sully illustrated the concept of hybridity, as his transformation from a colonial agent into a member of the indigenous community challenged the binary opposition between colonizer and colonized. The study concluded that Avatar functioned as a postcolonial narrative that criticized imperialist ideology and highlighted the importance of indigenous resistance, cultural identity, and environmental balance in the face of colonial and neo-colonial practices. Keywords: postcolonialism, colonial power, indigenous resistance, hybridity, film analysis